Analisis Kehidupan Pengamen Jalanan Dalam Aspek Pendidikan Di Kota Medan - Desy Novianti; Panny Chintya; Razika Nurul Aulia; Selfida Sunaria Purba; Vivi Artika Sari; Widya Utami Lubis; Dimas Budi Prabawa (Hikamatzu | Journal of Multidisciplinary, 2024)
The aim of this research is an analysis of the lives of street buskers in the educational aspect of Medan City. Qualitative research type. Based on the research results described in the discussion in the previous chapters, the author can conclude as follows: The existence of child buskers in the Medan City environment is influenced by two factors, namely economic factors and educational factors. Economic factors refer to their actions in busking based on poverty factors. The educational factor of street buskers refers to the way in which street buskers in Medan learn and develop their musical skills, including formal and informal education, as well as education outside of school.